2005
DOI: 10.1152/ajpendo.00382.2004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term calorie restriction reduces proton leak and hydrogen peroxide production in liver mitochondria

Abstract: . Longterm calorie restriction reduces proton leak and hydrogen peroxide production in liver mitochondria. Am J Physiol Endocrinol Metab 288: E674 -E684, 2005. First published November 23, 2004 doi: 10.1152/ajpendo.00382.2004.-Calorie restriction (CR) without malnutrition increases maximal life span in diverse species. It has been proposed that reduction in energy expenditure and reactive oxygen species (ROS) production could be a mechanism for life span extension with CR. As a step toward testing this theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 56 publications
7
64
0
1
Order By: Relevance
“…Such discrepancies were also found when CR was extended to 4-6 months 29,35 or 12-18 months. 26,28 In the present study, we found that isolated liver mitochondria from Lou/C rats, which display an inborn LCI, [1][2][3][7][8][9]14,15 produced more H 2 O 2 than Wistar rats fed ad libitum or even pair-fed. The enhanced H 2 O 2 generation displayed by Lou/C mitochondria takes place at many levels of the electron transport chain.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Such discrepancies were also found when CR was extended to 4-6 months 29,35 or 12-18 months. 26,28 In the present study, we found that isolated liver mitochondria from Lou/C rats, which display an inborn LCI, [1][2][3][7][8][9]14,15 produced more H 2 O 2 than Wistar rats fed ad libitum or even pair-fed. The enhanced H 2 O 2 generation displayed by Lou/C mitochondria takes place at many levels of the electron transport chain.…”
Section: Discussionmentioning
confidence: 50%
“…28 Nevertheless, the widespread notion of a reduced rate of H 2 O 2 generation by liver mitochondria with CR was recently challenged by some authors. 26,29 Thus, a similar reduction in caloric intake (B40%) for 4-8 weeks was found either to decrease 25 or to enhance 29 mitochondrial H 2 O 2 production. Such discrepancies were also found when CR was extended to 4-6 months 29,35 or 12-18 months.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…[51][52][53] Another large body of work demonstrates that ROS release from mitochondria or tissues from CR animals is decreased. 37,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Other publications found no changes in ROS production with CR 46,[68][69][70][71] and many propose that CR-induced decreases in ROS release depend on tissues examined, time on the diet, animal age when the diet was initiated, and gender. No experimental publication was located demonstrating that CR in rodents enhances ROS generation in non-inflammatory tissues.…”
Section: Effects Of Cr On Redox State In Vertebratesmentioning
confidence: 99%